The Polo‐like kinase Plx1 interacts with and inhibits Myt1 after fertilization of Xenopus eggs - Inoue, Daigo; Sagata, Noriyuki (The EMBO journal, 2005)
During the meiotic cell cycle in Xenopus oocytes, p90rsk, the downstream kinase of the Mos-MAPK pathway, interacts with and inhibits the Cdc2 inhibitory kinase Myt1. However, p90rsk is inactivated after fertilization due to the degradation of Mos. Here we show that the Polo‐like kinase Plx1, instead of p90rsk, interacts with and inhibits Myt1 after fertilization of Xenopus eggs. At the M phase of the embryonic cell cycle, Cdc2 phosphorylates Myt1 on Thr478 and thereby creates a docking site for Plx1. Plx1 can phosphorylate Myt1 and inhibit its kinase activity both in vitro and in vivo. The interaction between Myt1 and Plx1 is required, at least in part, for normal embryonic cell divisions. Finally, and interestingly, Myt1 is phosphorylated on Thr478 even during the meiotic cell cycle, but its interaction with Plx1 is largely inhibited by p90rsk‐mediated phosphorylation. These results indicate a switchover in the Myt1 inhibition mechanism at fertilization of Xenopus eggs, and strongly suggest that Plx1 acts as a direct inhibitory kinase of Myt1 in the mitotic cell cycles in Xenopus.
Gesehen am 22.06.2017